Analisis Faktor-Faktor yang Mempengaruhi Impulse Buying Pada Konsumen Karita Muslim Square Purwokerto - Mayla Surveyandini (Ekonomis: Journal of Economics and Business, 2021)
Unplanned purchases usually arise due to several factors, it could be price, lifestyle or following the push of a certain trend. Research on the effect of price discount, shopping lifestyle and fashion involvement on impulse buying on consumers Karita Muslim Square Purwokerto. This research is a quantitative study using 100 respondents who are consumers of Karita Muslim Square Purwokerto. This research uses multiple linear regression. The results show that price discount shopping lifestyle and fashion involvement have a positive and significant effect on impulse buying on consumers of Karita Muslim Square Purwokerto. The variable has a significant effect on impulse buying on Karita Muslim Square Purwokerto consumers. The variable has a significant effect on impulse buying on Karita Muslim Square Purwokerto consumers. Making shopping fun for consumers while still paying attention to purchases, this can be done by selecting the appropriate price, and products that are in accordance with trends or that are being liked by certain groups are fundamental to both consumers and producers